Development of Multiple Representation-based E-books on Physics Subjects in High Schools - Liszulfah Roza; Salsa Ariani Rodhiah; Zulherman Zulherman (UNIVERSITAS INDRAPRASTA PGRI, 2021)
The research was conducted to determine the feasibility of learning media in e-book applications that contain physics learning material for class X. This research was a research and development (R&D) using the ADDIE model. This research was conducted at SMAN 1 Siantan for students of class X MIA 2, SMAN 1 Palmatak for students of class X IPA 1, and SMKN 4 Arung Hijau for students of class X TKJ. Small-scale trials were conducted on students of SMAN 1 Palmatak class X IPA 1 with 15 students. Large-scale trials were conducted on students of SMAN 1 Palmatak class X IPA 1 with 25 students, SMAN 1 Siantan class X MIA 2 with 26 students, and SMKN 4 Arung Hijau class X TKJ with 9 students. Data collection was obtained using a Likert scale questionnaire. The data were quantitative in the form of the percentage of the feasibility of the media developed and qualitative data in the form of comments and suggestions for improvement given by respondents. In the feasibility test by material experts, the percentage is 92.66%. The feasibility test by media experts obtained a percentage of 76.06%. The percentage obtained through small-scale trials is 82.13%. Meanwhile, for large-scale trials, the percentage was 82.26%. It can be concluded that the learning media that has been developed by researchers can be said to be feasible to use.